Oxygen Isotopic Composition of Snow on Mizuho Plateau, Antarctica - Kikuo KATO; Okitsugu WATANABE; Kazuhide SATOW (National Institute of Polar Research, 1977)
Oxygen isotopic composition of snow samples taken on different dates at Syowa Station and Mizuho Camp, and at various stations during the traverses of the 15th Japanese Antarctic Research Expedition in 1974-1975 was determined. Daily variation of oxygen isotopic composition of snow at Syowa Station is caused mainly by the supply of ^O-rich water vapor on account of the approach of a depression. Seasonal variation of oxygen isotopic composition of snow at Syowa Station and Mizuho Camp is not always controlled only by the temperature of formation of the snow. An anomaly in oxygen isotopic composition of snow sampled at the stations along the traverse routes was found. The area where the anomaly was found is considered to be the boundary between the spheres of influence of Antarctic high and coastal low atmospheric pressure.